Sensorineural hearing loss in chronic suppurativve otitis media. - Sharma, Suman Chandra
Introduction: Inflammation of middle ear cleft is a common disorder. Chronic suppurative otitis media is typically a persistent disease, insidious in onset, often capable of causing severe destruction and irreversible sequel and manifests with deafness and discharge. The disease is defined as chronic suppurative otitis media when it is present for more than 3 months. Socioeconomic factors such as poor hygiene and nutrition have been suggested as a basis for widespread prevalence of chronic suppurative otiitis media. A national sample survey which was conducted in 1991 by the Department of ENT, Tribhuwan University Teaching Hospital(TUTH), Department of community Medicine, Institute of Medicine, Kathmandu and The Britain Nepal Otology Service (BRINOS) on the prevalence of deafness and ear diseases in Nepal. This is first and only of its kind. Salyan, Mugu, Banke, Jhapa, Sankhuwasabha and paanchthar Districts were surveyed. Total of 15845 persons were examined. Prevalence of chronic suppurative otitis media was found to be 8.1%. Further more it was found that one in five deafness was caused by chronic suppurative otitis media alone. Moreover , in school going age group. 50% of deafness was due to chronic suppurative otitis media. Even with advent of modern and powerful antimicrobials and aggressive surgical eradication of the disease, chronic suppurative otitis media has got significant morbidity and mortality. Some complications may initially be quite obvious while some complications may be quite subtle. Prasansuk and Hinchcliff(1982) described fur basic dysfunction in chronic suppurative otitis media which correlate hearing level with otoscopic appearance of the perforated tympanic membrane. These are impairment of the tympano-ossicular impedance matching mechanism, reduction of baffle effect on the round window, underlying middle ear pathology such as mucosal oedem, fluid, granulation, cholesteatoma, osteitis and ossicular necrosis which impair the tymopano-ossicular mechanism and underlying cochlear dysfunction. Classically hearing loss described in chronic suppurative otitis media has been due to loss in conductive component of hearing only. Politzer (1884) has been quoted to affirm that in advanced age of when the illness continues from infancy or when adhesive phenomena occur in the tympanic cavity, the perception of sound through the bone conduction is diminished or abolished. Thorbourn mentioned that tuning fork tests and an air and bone conduction audigraph usually shows conductive hearing loss but cochlear degeneration can develop insidiously in chronic otitis media. Verhoeven also made a statenment that cases of otitis media complicated by destructive process such a cholesteatoma, the resulting deafness can be either of perceptive or of a mixed type. All these statements, however, were largely anecdotal without any statistical data or reference to support it.